2022
DOI: 10.3390/pharmaceutics14030672
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Targeted Delivery of Exosomes to the Brain: Advantages and Challenges

Abstract: Delivering therapeutics to the central nervous system (CNS) is difficult because of the blood–brain barrier (BBB). Therapeutic delivery across the tight junctions of the BBB can be achieved through various endogenous transportation mechanisms. Receptor-mediated transcytosis (RMT) is one of the most widely investigated and used methods. Drugs can hijack RMT by expressing specific ligands that bind to receptors mediating transcytosis, such as the transferrin receptor (TfR), low-density lipoprotein receptor (LDLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 107 publications
0
28
0
Order By: Relevance
“…However, it has been demonstrated that when exosomes are administered externally (i.e., intravenously), a large fraction of systemically injected exosomes quickly become trapped in hepatic or splenic tissues due to their specialized subsets of phagocytic immune cells and extensive capillary network [ 58 ]. Because of this, many techniques have been developed to target these vesicles to the brain and improve their penetration through the BBB [ 59 , 60 , 61 ] ( Figure 2 ). The conjugation of specific ligands to the surface of exosomes increases the interaction with the target cells, and the addition of labeled fluorescent dyes or radioactive MRI agents is an efficient method for in vivo tracking [ 62 ].…”
Section: Exosomes Surface Functionalization For Brain Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been demonstrated that when exosomes are administered externally (i.e., intravenously), a large fraction of systemically injected exosomes quickly become trapped in hepatic or splenic tissues due to their specialized subsets of phagocytic immune cells and extensive capillary network [ 58 ]. Because of this, many techniques have been developed to target these vesicles to the brain and improve their penetration through the BBB [ 59 , 60 , 61 ] ( Figure 2 ). The conjugation of specific ligands to the surface of exosomes increases the interaction with the target cells, and the addition of labeled fluorescent dyes or radioactive MRI agents is an efficient method for in vivo tracking [ 62 ].…”
Section: Exosomes Surface Functionalization For Brain Deliverymentioning
confidence: 99%
“…The application of a natural receptor on exosomes’ luminal surface is widely used to increase the exosome transcytosis rate through the BBB. In this sense, TfR, INSR, and especially LDLRs are of great interest [ 61 ]. LDLR is widely expressed in the brain and is able to attach to different ligands (in addition to lipoprotein metabolism) to mediate endothelial transcytosis and address the endocytic cargo to the lysosomes [ 59 ].…”
Section: Exosomes Surface Functionalization For Brain Deliverymentioning
confidence: 99%
“…For this, drug-loaded liposomes are surface-functionalized or conjugated with suitable ligands (macromolecules such as peptides, antibodies, and aptamers), which enhance, at least in part, the pharmacokinetics and bio-distribution of liposomes [ 73 ]. The surface-functionalized ligand recognizes and binds to the specific receptors expressed on the brain endothelial cells' surface and penetrates across the BBB [ 74 , 75 ]. Commonly used receptors for brain targeting with liposomes are insulin, glucose, transferrin, l–type amino acid transporter-1, low-density lipoproteins, folate–receptors, etc.…”
Section: Receptor-mediated Transcytosismentioning
confidence: 99%
“…They act as a vehicle for intercellular communication and transport and are involved in synaptic plasticity, glutamate uptake, neuroprotection, and may promote axonal transport and modulate neuroinflammation [ 34 , 42 , 43 ]. EVs can overcome the blood-brain barrier (BBB) and enter the blood stream, particularly in neurodegenerative diseases and neuroinflammation, accompanied by BBB disruption [ 32 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%